The Effect of Service Quality and Price on Outpatient Satisfaction at the 3R Pratama Clinic in Sukabumi City - Cucu Hodijah; Umban Adi Jaya; Maryani Maryani (SEAN Institute, 2022)
This study aims to analyze the effect of service quality and price on patient satisfaction. The research method used in this study is a quantitative method. The data collection instrument used was a questionnaire using a sample of 68 respondents. The respondents in this study were patients who visited for treatment or health consultations to the 3R Primary Clinic. The data analysis method uses validity and reliability tests, classical assumptions, multiple linear regression, coefficient of determination and hypothesis testing. Based on the results of statistical testing, the following results were obtained: Service quality has a positive and significant influence on patient satisfaction. Price has a positive and significant effect on patient satisfaction. Quality of service and price Simultaneously using the F test is known to have a positive and significant effect on outpatient satisfaction at the 3R Pratama Clinic in Sukabumi City,